Optimasi Durasi Proyek dengan Penambahan Tenaga Kerja dan Jam Kerja Metode What If pada Proyek Pembangunan Gedung Soetandyo Universitas Airlangga - Mardiah, Arifa; Tjendani, Hanie Teki (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Project delay is one of the impacts of decreased performance, and this can result in schedule setbacks and other forms of losses that will be experienced by service providers and service users. The purpose of this research is to find the optimum duration in accelerating the duration for delays of 10%-40%. In the Airlangga University Soetandyo Building Construction Project, there was a deviation in field realization progress of -9.210% and the cause of the initial delay was deep foundation work. What if is one method or strategy that can help project delay management by adding workers and increasing working hours on jobs in the critical path that are experiencing delays. As for the 10% delay, 78 additional workers and 19 additional working hours were obtained, for the 20% delay, 223 additional workers and 25 additional working hours were obtained, and for the 30% delay, 205 additional workers and 39 additional working hours were obtained